Biosensor for measuring the anti-diabetic potential of medicinal plants - Md. Mohiuddin (School of Bioprocess Engineering, University Malaysia Perlis, 2014)
The results showed that the inhibition obtained in the presence of Tebengau plant extracts is higher than that obtained with Acarbose, Cemumar and Kedondong. The kinetic of immobilized and non-immobilized enzyme was measured using Lineweaver-Burk equation. The CV response for inhibition of AG enzyme activity within the biosensor by Tebengau plant extracts showed a linear relationship in the range from 0.5 - 3.5 mg/mL and an inhibition detection limit was 0.5 mg/mL. The biosensor exhibited good sensitivity (1.037 uA/mg Tebengau plant extracts) and rapid response within 22 seconds. The biosensor retains about 79.16 % its initial activity even after 30 days when stored at 40C.